O Efeito moderador do sistema de controle de vendas na adoção da ambidestria serviços-vendas - Faia, Valter da Silva (2014)
The demands imposed by the environment conduct organizations to achieve seemingly conflicting goals that compete for resources. Organizations that demonstrate this capacity are called ambidextrous organizations. The paper was based on the concept of contextual ambidexterity, which is the result of organizational and individual factors that enable and encourage individuals to make their own judgment about how to apply their resources between conflicting goals. The theme of this research was the service-sales ambidexterity. It refers to the ability of an individual to engage simultaneously in both service and sales activity. The hypotheses developed consider that the individual's regulatory modes influence in the adoption of ambidextrous behavior, which in turn, influences individual performance in terms of sales and efficiency. These relationships were also hypothesized moderated by the sales control systems. A survey was executed with 162 bank managers. The results indicate that the individual regulatory modes are positively related to the ambidextrous behavior. The locomotion profile presented a direct relationship and a moderated relationship by assessment profile with ambidextrous behavior, supporting the hypotheses. The hypothesis that the ambidextrous behavior is positively related with sales performance was also supported. However, the hypothesis that ambidexterity is negatively related with efficiency was not confirmed. The assumption that the sales control system moderates the relationship the antecedent relationship of ambidextrous behavior was supported. Although, it was not identified a moderating effect in the relationship between ambidexterity and the measures of sales performance and efficiency, but rather a direct effect of sales control system on these measures. Additional analyses were also performed.